A case report of a child with pulmonary hypertension associated with SARS-CoV-2 infection - Okunushi, Kentaro; Kobayashi, Hironobu; Yoh, Yuri; Kunimatsu, Masaya; Shiohama, Tadashi; Takatani, Tomozumi; Hamada, Hiromichi (Frontiers in Pediatrics, 2024)
We encountered a pediatric case of pulmonary hypertension triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. A 14-year-old girl was brought to the emergency department of our hospital with fever, respiratory distress, and impaired consciousness. She tested positive for SARS-CoV-2 upon a polymerase chain reaction examination and had prolonged hypoxemia without pneumonia. An echocardiography revealed elevated right ventricular pressure. She was diagnosed with pilocytic astrocytoma at the age of 10 years and underwent a resection of a pituitary tumor. Hormone replacement therapy was administered postoperatively, but her growth hormones were not activated because of concerns about tumor recurrence. Echocardiography at the age of 13 years showed normal right ventricular pressure. On admission, she had an abnormal liver function, elevated liver fibrosis markers, a decreased platelet count, and hepatosplenomegaly, suggesting pulmonary and portal hypertension. The diagnosis was pulmonary hypertension associated with SARS-CoV-2 infection. The mechanism of the pulmonary hypertension was thought to be portal hypertension owing to growth hormone deficiency and SARS-CoV-2 infection. The patient's symptoms improved with oxygenation and bed rest without additional targeted pulmonary hypertension therapy, and her right ventricular pressure decreased. This case demonstrates that a pediatric patient with subclinical pulmonary hypertension may develop pulmonary hypertension triggered by SARS-CoV-2 infection.